Infectious complications of laparoscopic and robotic hysterectomy: a systematic literature review and meta-analysis. (March 2019) - Marra, Alexandre R; Puig-Asensio, Mireia; Edmond, Michael B; Schweizer, Marin L; Bender, David
Abstract : Objective: We performed a systematic review of the literature and meta-analysis of the infectious complications of hysterectomy, comparing robotic-assisted hysterectomy to conventional laparoscopic-assisted hysterectomy. Methods: We searched PubMed, CINAHL, CDSR, and EMBASE through July 2018 for studies evaluating robotic-assisted hysterectomy, laparoscopic-assisted hysterectomy, and infectious complications. We employed random-effect models to obtain pooled OR estimates. Heterogeneity was evaluated with I 2 estimation and the Cochran Q statistic. Pooled ORs were calculated separately based on the reason for hysterectomy (eg, benign uterine diseases, endometrial cancer, and cervical cancer). Results: Fifty studies were included in the final review for the meta-analysis with 176 016 patients undergoing hysterectomy. There was no statistically significant difference in the number of infectious complication events between robotic-assisted hysterectomy and laparoscopic-assisted hysterectomy (pooled OR 0.97; 95 % CI 0.74 to 1.28). When we performed a stratified analysis, similar results were found with no statistically significant difference in infectious complications comparing robotic-assisted hysterectomy to laparoscopic-assisted hysterectomy among patients with benign uterine disease (pooled OR 1.10; 95 % CI 0.70 to 1.73), endometrial cancer (pooled OR 0.97; 95 % CI 0.55 to 1.73), or cervical cancer (pooled OR 1.09; 95 % CI 0.60 to 1.97). Conclusion: In our meta-analysis the rate of infectious complications associated with robotic-assisted hysterectomy was no different than that associated with conventional laparoscopic-assisted hysterectomy.